Effect of planting method and weeding regime on the performance of transplant Aman rice (Progressive Agriculture, 2016)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during July to December 2014 to evaluate the effect of planting method and weeding regime on the performance of transplant Aman rice. Two planting methods viz. line transplanting and haphazard transplanting and six weed control treatments viz. no weeding, one hand weeding at 21 DAT, two hand weeding at 21 and 42 DAT, pre-emergence herbicide Rifit 500 EC at 7 DAT, pre-emergence herbicide Rifit 500 EC at 7 DAT + one hand weeding at 42 DAT and weed free were used as experimental treatments with three replications in a randomized complete block design (RCBD). Planting methods, weeding treatment and their interaction significantly influenced most of the crop characters and yield components of transplant Aman rice. The highest effective tillers hill-1 (9.30),grain panicle-1 (185.4), grain yield (3.89 t ha-1), straw yield (5.57 t ha-1), biological yield (9.54t ha-1) and harvest index (41.08) were obtained from line transplanting. Complete weed free treatment produced the highest total tillers hill-1 (12.37), effective tillers hill -1 (9.89), grain yield (4.11 tha-1) and biological yield (9.94 t ha-1).The highest total tillers hill-1(13.07), effective tillers hill -1(10.70), grain yield (4.50t ha-1) and biological yield (10.79 t ha-1) were obtained from line transplanting under weed free treatment. Results revealed that line transplanting with pre-emergence herbicide Rifit 500 EC at 7 DAT + one hand weeding at 42 DAT might be used to control weeds effectively and to get higher yield of transplant Aman rice.Progressive Agriculture 27 (3): 249-255, 2016